Ceftriaxone‐resistantSalmonellaTyphi carries an IncI1‐ST31 plasmid encoding CTX‐M‐15. Issue 5 (May 2018) - Djeghout, Bilal; Saha, Senjuti; Sajib, Mohammad Saiful Islam; Tanmoy, Arif Mohammad; Islam, Maksuda; Kay, Gemma L.; Langridge, Gemma C.; Endtz, Hubert P.; Wain, John; Saha, Samir K.
Abstract : Purpose. : Ceftriaxone is the drug of choice for typhoid fever and the emergence of resistant Salmonella Typhi raises major concerns for treatment. There are an increasing number of sporadic reports of ceftriaxone‐resistant S . Typhi and limiting the risk of treatment failure in the patient and outbreaks in the community must be prioritized. This study describes the use of whole genome sequencing to guide outbreak identification and case management. Methodology. : An isolate of ceftriaxone‐resistant S . Typhi from the blood of a child taken in 2000 at the Popular Diagnostic Center, Dhaka, Bangladesh was subjected to whole genome sequencing, using an Illumina NextSeq 500 and analysis using Geneious software. Results/Key findings. : Comparison with other ceftriaxone‐resistant S . Typhi revealed an isolate from the Democratic Republic of the Congo in 2015 as the closest relative but no evidence of an outbreak. A plasmid belonging to incompatibility group I1 (IncI1‐ST31) which included bla CTX‐M‐15 (ceftriaxone resistance) associated with ISEcp‐1 was identified. High similarity (90 %) was seen with pS115, an IncI1 plasmid from S . Enteritidis, and with pESBL‐EA11, an incI1 plasmid from E. coli (99 %) showing that S. Typhi has access to ceftriaxone resistance through the acquisition of common plasmids. Conclusions. : The transmission of ceftriaxone resistance from E. coli to S. Typhi is of concern because of clinical resistance to ceftriaxone, the main stay of typhoid treatment. Whole genome sequencing, albeit several years after the isolation, demonstrated the success of containment but clinical trials with alternative agents are urgently required.